Preventing Violence by Teachers in Primary Schools: Study Protocol for a Cluster Randomized Controlled Trial in Haiti - López García, Ana Isabel; Scharpf, Florian; Hoeffler, Anke; Hecker, Tobias (Frontiers in Public Health, 2022)
Context: Although teacher violence at schools is a serious problem in Haiti, there is a lack of systematic evidence on the effectiveness of school-based interventions in reducing teacher violence in this low-income country. Objective: To test the effectiveness of the preventative intervention Interaction Competencies with Children for Teachers (ICC-T) aiming to reduce teachers’ use of violent disciplinary strategies and to improve their interaction competences with children in the Haitian context. Design, setting, participants. The study is designed as a two-arm matched cluster randomized controlled trial. The sample consists of 468 teachers and 1,008 children from 36 (community and public) primary schools around Cap-Haitien (Département du Nord) in Haiti. Data will be collected in three phases, before the intervention, and 6 and 18 months after. Intervention: In the group of intervention schools, ICC-T will be delivered as a 5-day training workshop. Workshop sessions are divided into five modules: 1) improving teacher-student interactions, 2) maltreatment prevention, 3) effective discipline strategies, 4) identifying and supporting burdened students, and 5) practice of all the above components. Main Outcome Measure: The main outcome measure is teacher violence assessed in two ways: (i) teachers’ self-reported use of violence, and (ii) children’s self-reported experiences of violence by teachers. Conclusions: Prior evaluations of ICC-T had been conducted in sub-Saharan Africa with promising results. This study will test for the first time the effectiveness of this intervention outside the context of sub-Saharan Africa. Trial registration: The trial was registered at clinicaltrials.org under the ClinicalTrials.gov identifier NCT05081622 on October 18, 2021